Tea for two - O'Connor, Jane.; Bracken, Carolyn (New York : HarperFestival, 2012)
When Nancy joins her friend Bree for a tea party and her friend's teapot is broken, Nancy worries that their friendship may be ruined.
Accelerated Reader AR
Keywords: Afternoon teas -- Juvenile fiction; Parties -- Juvenile fiction; Friendship -- Juvenile fiction; Fancy Nancy (Fictitious character) -- Juvenile fiction